Leadership for social justice? : exploring training and support needs of Indian school principals - Ranjan, Pukhraj (2017)
School Leadership is a fairly unexplored area within the education discourse, especially in developing countries like India. The purpose of this research study is to identify the training and support needs of Indian school principals, working with students from marginalized, under-resourced communities. This purpose is met by attaining a holistic understanding of a school leader’s perceptions about his/her role and responsibilities, challenges, underlying mindsets and opportunities. For the study, five school principals were interviewed and the data analysis followed a qualitative, content analysis methodology. The principals have different personal backgrounds, cities, years of experience and school types, who when interviewed within a semi-structured format provided a variety of perspectives. The results of the study were explored specifically with respect to the research questions, and generally under the consideration of the Capability Approach (CA), propounded by Sen (1999). The results of the study reveal the demanding role and responsibilities of Indian school principals, especially ones working within the government or public-private partnership school setups, catering to marginalized communities. The results additionally provided insights into the challenges, opportunities and underlying mindsets of the principals. A perspective of social justice was noticed as the results showcased an activist approach to school leadership. The study concludes with elucidating the functionings valuable as well as the factors influencing the support and training needs of Indian school principals using the CA. Furthermore, the recommendations from the data are analyzed against national standards set for school leadership development by the National Centre for School Leadership (NCSL) in India. The study closes with a comment on the need for social justice approach to leadership in the Indian school leadership space.